A method for preparing a graphene composite conductive agent for battery positive electrode material
By using graphene composite conductive agent in the positive electrode material of lithium-ion battery, using conductive mica powder, carbon black and barium sulfate as conductive additives, the existing conductive agents have been solved in the large amount of additives, high price and difficulty in dispersion, and more efficient electrochemical performance and cycling performance have been achieved.
Patent Information
- Application Number
- CN202210848168.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-07-19
AI Technical Summary
The conductive agents of existing lithium-ion batteries such as acetylene black and carbon nanotubes have problems such as high addition, expensive and difficult to disperse while improving electrode activity and conductivity.
The preparation method of graphene composite conductive agent is adopted, and high-voltage dispersion is carried out by limiting conductive mica powder, conductive carbon black, and conductive barium sulfate as conductive additives, combined with butyl acetate, dispersant and conductive polymer agents, to ensure uniform dispersion of graphene and conductive additives in the positive electrode material of the battery.
It effectively improves the surface electronic conductivity of the positive electrode active material, improves the electrochemical performance of the electrode, and improves the cycle performance of the battery and the impedance performance of the electrode.
Smart Images

Figure BDA0003752217820000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery material preparation, and in particular relates to a method for preparing a graphene composite conductive agent for battery positive electrode materials. Background Art
[0002] Lithium-ion batteries have the advantages of high specific energy and no memory effect. In recent years, they have been favored as a new energy source and have developed rapidly. As the technology matures, people's requirements for lithium-ion batteries are getting higher and higher.
[0003] Lithium-ion batteries in the prior art mainly use conductive graphite, acetylene black and carbon nanotubes as conductive agents. Acetylene black is a chain composed of spherical amorphous carbon particles. It is the most widely used conductive agent and is inexpensive. However, in order to achieve the purpose of enhancing the mutual contact between electrode active substances, a large amount of addition is required, which causes a decrease in electrode capacity. Carbon nanotubes are linear one-dimensional carbonaceous materials. Compared with acetylene black, carbon nanotubes have better conductivity and are added in a small amount. However, carbon nanotubes are currently expensive and have the disadvantage of being difficult to disperse when used as a conductive agent, which needs further improvement. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a graphene composite conductive agent for battery positive electrode materials.
[0005] The present invention adopts the following technical solution:
[0006] A method for preparing a graphene composite conductive agent for battery positive electrode materials,
[0007] The graphene composite conductive agent is composed of the following raw materials in parts by weight: 140-160 parts of graphene, 350-420 parts of butyl acetate, 50-70 parts of conductive additive, 30-45 parts of dispersant, 5-8 parts of conductive polymer agent, and 2-3 parts of dispersant.
[0008] The conductive additive is composed of conductive mica powder, conductive carbon black and conductive barium sulfate in a mass ratio of 4:7-8:1;
[0009] The preparation method thereof comprises the following steps:
[0010] Step 1: first soak the conductive mica powder with 100-120 parts of butyl acetate for 18-24 hours, then add conductive carbon black and conductive barium sulfate, and stir for 20-30 minutes to obtain premix A;
[0011] Step 2: adding graphene to the remaining butyl acetate, stirring for 15-20 minutes, then adding premix A, stirring for 30-40 minutes, to obtain premix B;
[0012] Step 3, adding the remaining other raw materials to the premix B, mixing and stirring for 20-30 minutes, performing high-pressure dispersion treatment, and homogenizing and stirring for 3-6 hours to obtain the graphene composite conductive agent.
[0013] Preferably, the dispersing aid is composed of polyoxyethylene stearate, polyvinyl alcohol, and organic bentonite in a mass ratio of 0.4-0.6:0.2-0.3:1.
[0014] Preferably, the conductive polymer is polyaniline or polyacetylene.
[0015] Preferably, the dispersant is composed of polyoxyethylene castor oil and polyvinyl pyrrolidone in a mass ratio of 2:1.
[0016] Preferably, the graphene is a black powder with a particle size distribution of 10nm-100um and a specific surface area of 80-120m 2 / g.
[0017] Preferably, the viscosity of the graphene composite conductive agent is less than 6000 cps and the pH value is 6.3-7.6.
[0018] Preferably, in step three, the pressure of the high-pressure dispersion treatment is 21000 PSI.
[0019] Preferably, in step 1, the revolution rate of stirring is 20r / min-30r / min, and the rotation speed is 1000r / min-1200r / min.
[0020] Preferably, in step 2, the revolution rate of stirring is 35r / min-50r / min, and the rotation speed is 1200r / min-1500r / min.
[0021] It can be seen from the above description of the present invention that, compared with the prior art, the present invention has the following beneficial effects: the present invention limits the combination of conductive mica powder, conductive carbon black, and conductive barium sulfate as the conductive additive of graphene, which can be fully filled between graphene sheets without agglomeration, effectively improving the surface electronic conductivity of the positive electrode active material and improving the electrochemical performance of the electrode;
[0022] The composition of the dispersing aid and the coordination of the dispersant are limited, so that the graphene and the conductive aid are in a very good dispersed state, and the upper layer chromatography and lower layer sedimentation phenomena of the composite conductive agent slurry are effectively improved. Among them, the dispersant is added with polyoxyethylene castor oil, which can effectively improve the anti-sedimentation property of the conductive mica powder during the dispersion process, thereby ensuring that the conductive mica powder can be evenly and fully filled between the graphene sheets, so that the impedance of the prepared positive electrode plate is significantly reduced, the polarization is smaller, and the cycle performance of the battery is improved. DETAILED DESCRIPTION
[0023] The present invention is further described below through specific implementation modes.
[0024] A graphene composite conductive agent for battery positive electrode material is composed of the following raw materials in parts by weight: 140-160 parts of graphene, 350-420 parts of butyl acetate, 50-70 parts of conductive aid, 30-45 parts of dispersant, 5-8 parts of conductive polymer agent, and 2-3 parts of dispersant. The viscosity of the graphene composite conductive agent is less than 6000cps, and the pH value is 6.3-7.6.
[0025] Graphene is a black powder with a particle size distribution of 10nm-100um and a specific surface area of 80-120m 2 / g.
[0026] The conductive additive is composed of conductive mica powder, conductive carbon black and conductive barium sulfate in a mass ratio of 4:7-8:1.
[0027] The dispersing aid is composed of polyoxyethylene stearate, polyvinyl alcohol and organic bentonite in a mass ratio of 0.4-0.6:0.2-0.3:1.
[0028] The conductive polymer agent is polyaniline or polyacetylene.
[0029] The dispersant is composed of polyoxyethylene castor oil and polyvinyl pyrrolidone in a mass ratio of 2:1.
[0030] The preparation method thereof comprises the following steps:
[0031] Step 1: first soak the conductive mica powder with 100-120 parts of butyl acetate for 18-24 hours, then add conductive carbon black and conductive barium sulfate, stir for 20-30 minutes, and obtain premix A. The stirring revolution speed is 20r / min-30r / min, and the rotation speed is 1000r / min-1200r / min;
[0032] Step 2: Add graphene to the remaining butyl acetate, stir for 15-20 minutes, then add premix A, stir for 30-40 minutes to obtain premix B, the stirring revolution rate is 35r / min-50r / min, and the rotation speed is 1200r / min-1500r / min;
[0033] Step 3: add the remaining other raw materials to the premix B, mix and stir for 20-30 minutes, perform high-pressure dispersion treatment at a pressure of 21000PSI, and homogenize and stir for 3-6 hours to obtain the graphene composite conductive agent.
[0034] Example 1
[0035] A graphene composite conductive agent for battery positive electrode material is composed of the following raw materials in parts by weight: 140 parts of graphene, 420 parts of butyl acetate, 70 parts of conductive aid, 30 parts of dispersant, 8 parts of conductive polymer agent, and 2 parts of dispersant; wherein the viscosity of the graphene composite conductive agent is less than 6000cps, and the pH value is 6.3-7.6.
[0036] Graphene is a black powder with a particle size distribution of 10nm-100um and a specific surface area of 80-120m 2 / g.
[0037] The conductive additive is composed of conductive mica powder, conductive carbon black and conductive barium sulfate in a mass ratio of 4:7:1.
[0038] The dispersing aid is composed of polyoxyethylene stearate, polyvinyl alcohol and organic bentonite in a mass ratio of 0.4:0.2:1.
[0039] The conductive polymer is polyaniline.
[0040] The dispersant is composed of polyoxyethylene castor oil and polyvinyl pyrrolidone in a mass ratio of 2:1.
[0041] The preparation method thereof comprises the following steps:
[0042] Step 1: first soak the conductive mica powder with 100 parts of butyl acetate for 18 hours, then add conductive carbon black and conductive barium sulfate, and stir for 20 minutes to obtain premix A. The stirring revolution speed is 30r / min and the rotation speed is 1200r / min;
[0043] Step 2: adding graphene to the remaining butyl acetate, stirring for 15 minutes, then adding premix A, stirring for 30 minutes to obtain premix B, the stirring revolution speed is 50r / min, and the rotation speed is 1500r / min;
[0044] Step 3: add the remaining other raw materials to the premix B, mix and stir for 20 minutes, perform high-pressure dispersion treatment at a pressure of 21000PSI, and homogenize and stir for 6 hours to obtain the graphene composite conductive agent.
[0045] Example 2
[0046] A graphene composite conductive agent for battery positive electrode material is composed of the following raw materials in parts by weight: 160 parts of graphene, 350 parts of butyl acetate, 50 parts of conductive aid, 45 parts of dispersant, 5 parts of conductive polymer agent, and 3 parts of dispersant; wherein the viscosity of the graphene composite conductive agent is less than 6000cps, and the pH value is 6.3-7.6.
[0047] Graphene is a black powder with a particle size distribution of 10nm-100um and a specific surface area of 80-120m 2 / g.
[0048] The conductive additive is composed of conductive mica powder, conductive carbon black and conductive barium sulfate in a mass ratio of 4:8:1.
[0049] The dispersing aid is composed of polyoxyethylene stearate, polyvinyl alcohol and organic bentonite in a mass ratio of 0.6:0.3:1.
[0050] The conductive polymer is polyacetylene.
[0051] The dispersant is composed of polyoxyethylene castor oil and polyvinyl pyrrolidone in a mass ratio of 2:1.
[0052] The preparation method thereof comprises the following steps:
[0053] Step 1: first soak the conductive mica powder with 120 parts of butyl acetate for 24 hours, then add conductive carbon black and conductive barium sulfate, and stir for 30 minutes to obtain premix A. The stirring speed is 20r / min and the rotation speed is 1000r / min.
[0054] Step 2: adding graphene to the remaining butyl acetate, stirring for 20 minutes, then adding premix A, stirring for 40 minutes to obtain premix B, the stirring revolution speed is 35 r / min, and the rotation speed is 1200 r / min;
[0055] Step 3: add the remaining other raw materials to the premix B, mix and stir for 30 minutes, perform high-pressure dispersion treatment at a pressure of 21000PSI, and homogenize and stir for 3 hours to obtain the graphene composite conductive agent.
[0056] Example 3
[0057] A graphene composite conductive agent for battery positive electrode material is composed of the following raw materials in parts by weight: 150 parts of graphene, 390 parts of butyl acetate, 60 parts of conductive aid, 36 parts of dispersant, 7 parts of conductive polymer agent, and 2.5 parts of dispersant; wherein the viscosity of the graphene composite conductive agent is less than 6000cps, and the pH value is 6.3-7.6.
[0058] Graphene is a black powder with a particle size distribution of 10nm-100um and a specific surface area of 80-120m 2 / g.
[0059] The conductive additive is composed of conductive mica powder, conductive carbon black and conductive barium sulfate in a mass ratio of 4:7.6:1.
[0060] The dispersing aid is composed of polyoxyethylene stearate, polyvinyl alcohol and organic bentonite in a mass ratio of 0.5:0.25:1.
[0061] The conductive polymer is polyacetylene.
[0062] The dispersant is composed of polyoxyethylene castor oil and polyvinyl pyrrolidone in a mass ratio of 2:1.
[0063] The preparation method thereof comprises the following steps:
[0064] Step 1: first soak the conductive mica powder with 110 parts of butyl acetate for 21 hours, then add conductive carbon black and conductive barium sulfate, and stir for 25 minutes to obtain premix A. The stirring revolution speed is 25r / min and the rotation speed is 1100r / min;
[0065] Step 2: adding graphene to the remaining butyl acetate, stirring for 18 minutes, then adding premix A, stirring for 35 minutes to obtain premix B, the stirring revolution speed is 42 r / min, and the rotation speed is 1350 r / min;
[0066] Step 3: add the remaining other raw materials to the premix B, mix and stir for 250 minutes, perform high-pressure dispersion treatment at a pressure of 21000PSI, and homogenize and stir for 4.5 hours to obtain the graphene composite conductive agent.
[0067] Comparative Example 1
[0068] The preparation method is basically the same as that of Example 3, except that no conductive additive is added to the raw material composition.
[0069] Comparative Example 2
[0070] The preparation method is basically the same as that of Example 3, except that the conductive additive is carbon black.
[0071] The composite conductive additives obtained in Examples 1-3 and Comparative Examples 1-2 were used to prepare positive electrode sheets according to conventional methods, and then the conductivity and electrochemical performance of the positive electrode sheets were measured. The charge and discharge voltage range was 2.75 to 4.2 V, and the test temperature was 35° C. The cycle was repeated 500 times at 1C charge and 6C discharge conditions. The following data were obtained:
[0072] Table 1 Test data of each embodiment
[0073]
[0074] It can be seen from the above table that the impedance of the positive electrode sheet prepared by the composite conductive agent of the present application is significantly reduced, the polarization is smaller, and the cycle performance of the battery is significantly improved; by limiting the conductive mica powder, conductive carbon black, and conductive barium sulfate as the conductive additive of graphene, it can be fully filled between the graphene sheets without agglomeration, effectively improving the surface electronic conductivity of the positive electrode active material, and improving the electrochemical performance of the electrode.
[0075] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of implementation of the present invention. That is, equivalent changes and modifications made according to the scope of the patent application of the present invention and the contents of the specification should still fall within the scope covered by the patent of the present invention.
Claims
1. A method for preparing a graphene composite conductive agent for a positive electrode material of a battery, characterized in that: The graphene composite conductive agent is composed of the following raw materials in parts by weight: 140-160 parts of graphene, 350-420 parts of butyl acetate, 50-70 parts of conductive additive, 30-45 parts of dispersant, 5-8 parts of conductive polymer agent, and 2-3 parts of dispersant. The conductive additive is composed of conductive mica powder, conductive carbon black and conductive barium sulfate in a mass ratio of 4:7-8:1; The preparation method thereof comprises the following steps: Step 1: first soak the conductive mica powder with 100-120 parts of butyl acetate for 18-24 hours, then add conductive carbon black and conductive barium sulfate, and stir for 20-30 minutes to obtain premix A; Step 2: adding graphene to the remaining butyl acetate, stirring for 15-20 minutes, then adding premix A, stirring for 30-40 minutes, to obtain premix B; Step 3, adding the remaining other raw materials to the premix B, mixing and stirring for 20-30 minutes, performing high-pressure dispersion treatment, and homogenizing and stirring for 3-6 hours to obtain the graphene composite conductive agent.
2. The method for preparing a graphene composite conductive agent for a positive electrode material of a battery according to claim 1, characterized in that: The dispersing aid is composed of polyoxyethylene stearate, polyvinyl alcohol and organic bentonite in a mass ratio of 0.4-0.6:0.2-0.3:
1.
3. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: The conductive polymer agent is polyaniline or polyacetylene.
4. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: The dispersant is composed of polyoxyethylene castor oil and polyvinyl pyrrolidone in a mass ratio of 2:
1.
5. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: The graphene is a black powder with a particle size distribution of 10nm-100um and a specific surface area of 80-120m 2 / g.
6. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: The viscosity of the graphene composite conductive agent is less than 6000 cps, and the pH value is 6.3-7.
6.
7. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: In step 3, the pressure of the high pressure dispersion treatment is 21000PSI.
8. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: In step 1, the stirring revolution speed is 20r / min-30r / min, and the rotation speed is 1000r / min-1200r / min.
9. The method for preparing a graphene composite conductive agent for battery positive electrode material according to claim 1, characterized in that: In step 2, the stirring revolution speed is 35r / min-50r / min, and the rotation speed is 1200r / min-1500r / min.
Citation Information
Patent Citations
Heterogeneous graphene conductive agent special for lithium battery and preparation method thereof
CN106450330A
Preparation method of graphene composite conductive agent for lithium ion battery positive electrode material
CN108711625A